2016
DOI: 10.1093/mnras/stw2063
|View full text |Cite
|
Sign up to set email alerts
|

AGN–starburst evolutionary connection: a physical interpretation based on radiative feedback

Abstract: Observations point towards a close connection between nuclear starbursts, active galactic nuclei (AGN), and outflow phenomena. An evolutionary sequence, starting from a dust-obscured ultra-luminous infrared galaxy and eventually leading to an unobscured optical quasar, has been proposed and discussed in the literature. AGN feedback is usually invoked to expel the obscuring gas and dust in a blow-out event, but the underlying physical mechanism remains unclear. We consider AGN feedback driven by radiation press… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…The derived R l values are 3 × 10 −3 pc and 3 × 10 −4 pc, respectively, which are all much smaller than the torus sublimation radius, thereby conflicting with our initial assumption that the outflows are launched in the torus. In addition, the fully absorbed scenario is also inconsistent with observations (Leighly et al 2009); and more sophisticated calculations of radiation pressure implementing on dusty gas from the torus also indicated that the typical maximum outflow velocity is a few thousand km s −1 and hardly reaches v > 10000 km s −1 , even if an enhanced dust to gas ratio is adopted for luminous dusty quasars (e.g., Ishibashi & Fabian 2016;Ishibashi et al 2017). Therefore, we argue that the outflows in WPVS 007 may most probable to be launched in the region closer to the black hole, and the torus origin maybe less likely.…”
Section: Bal Velocity and Outflow Launch Radiusmentioning
confidence: 98%
“…The derived R l values are 3 × 10 −3 pc and 3 × 10 −4 pc, respectively, which are all much smaller than the torus sublimation radius, thereby conflicting with our initial assumption that the outflows are launched in the torus. In addition, the fully absorbed scenario is also inconsistent with observations (Leighly et al 2009); and more sophisticated calculations of radiation pressure implementing on dusty gas from the torus also indicated that the typical maximum outflow velocity is a few thousand km s −1 and hardly reaches v > 10000 km s −1 , even if an enhanced dust to gas ratio is adopted for luminous dusty quasars (e.g., Ishibashi & Fabian 2016;Ishibashi et al 2017). Therefore, we argue that the outflows in WPVS 007 may most probable to be launched in the region closer to the black hole, and the torus origin maybe less likely.…”
Section: Bal Velocity and Outflow Launch Radiusmentioning
confidence: 98%
“…Banerji et al 2015). In a broader context, we have proposed how such radiative feedback, which directly acts on the obscuring dusty gas, may provide a natural physical interpretation for the observed co-evolutionary sequence (Ishibashi & Fabian 2016). Therefore AGN radiative feedback naturally fits in the global picture of 'black hole-host galaxy coevolution' scenarios.…”
Section: The Importance Of Radiation Trappingmentioning
confidence: 99%
“…To demonstrate that the numerical setup is performing as expected we require an analytic solution to compare with. As an AGN feedback channel, radiation pressure on dust has been well studied via analytical models (Murray et al 2005;Ishibashi & Fabian 2015;Thompson et al 2015;Ishibashi & Fabian 2016;Ishibashi et al 2018). We follow the analytic model presented in Ishibashi & Fabian (2015) and Thompson et al (2015), also see Costa et al (2018a).…”
Section: Analytic Solutionmentioning
confidence: 99%